Foundations of generic optimization. Volume 2: Applications of Fuzzy Control, Genetic Algorithms and Neural Networks - Lowen, R. (Springer, 2017)
This is a comprehensive overview of the basics of fuzzy control, which also brings together some recent research results in soft computing, in particular fuzzy logic using genetic algorithms and neural networks. This book offers researchers not only a solid background but also a snapshot of the current state of the art in this field.